Portulaca oleracea methanolic extract attenuate bile duct ligation-induced acute liver injury through hepatoprotective and anti-inflammatory effects. Issue 7 (July 2021) - Moslemi, Zahra; Bahrami, Mina; Hosseini, Ebrahim; Mansourian, Mahboubeh; Daneshyar, Zahra; Eftekhari, Mahdieh; Shakerinasab, Nasrin; Asfaram, Arash; Panahi kokhdan, Esmaeel; Barmoudeh, Zahra; Doustimotlagh, Amir Hossein
Abstract: Introduction: Cholestasis is a liver disease caused by a malfunction of the hepato-biliary system. Oxidative stress as a systemic complication is the main characteristic of cholestasis. The aim of this study was to evaluate the anti-inflammatory and hepatoprotective effects of Portulaca oleracea (PO) methanolic extract on liver dysfunction and tissue damage induced by bile duct ligation (BDL) in rats. Materials and methods: Twenty-eight male Wistar rats were randomly divided into four groups: sham control (SC), BDL alone, SC plus 500 mg/kg methanolic extract of PO orally for 1 week, and BDL plus 500 mg/kg methanolic extract of PO orally for 1 week. After 1 week, the animals were anesthetized, and the liver and blood samples were taken from each animal. Biochemical parameters, oxidative stress biomarkers, histopathological changes, as well as the gene expression of IL-1, TNF-α, TGF-β, and α-SMA have been evaluated. Results: The methanolic extract of PO at a dose of 500 mg/kg significantly decreased the plasma levels of aminotransferases, alkaline phosphatase as compared to BDL group (P < 0.05), while it had no significant effect on the levels of oxidative stress markers in the hepatic tissue. The plasma level of malondialdehyde and ferric-reducing antioxidant power were markedly elevated in the BDL group in comparison to SC group (P < 0.05), while treatment with PO significantly reduced these markers (P < 0.05). The administration of PO attenuated hydroxyproline content, bile duct proliferation, and inflammation score in the cholestatic liver in contrast to non-treated BDL rats (P < 0.05). Moreover, the methanolic extract of PO markedly declined the expression of TNF-α and TGF-β pro inflammatory genes in contrast to BDL rats. Conclusions: Taken together, our findings showed that PO attenuated liver injury by decreasing liver function tests, inflammation, and hydroxyproline content. As a result, it is suggested that PO can be applied in cholestatic liver damage as a therapeutic or adjuvant agent. Abstract : Cholestasis; Portulaca oleracea ; Oxidative stress, Anti-inflammatory agents, Bile ducts, Rats.